On A Possible Mechanism For The Start Or Resumption Of Activity Of Radio Galaxies In Clusters Of Galaxies - Andreasyan, R. R.; Abrahamyan, H. V.; Paronyan, G. M.; Mikayelyan, G. A.; Mickaelian, A. M. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We study the close proximity of the well-known and well-studied 3C31 class FRI radio galaxy in order to reveal the influence of the environment on an extragalactic radio source. It was shown that about 110 million years ago the galaxies NGC 380 and NGC 386 were located near the galaxy NGC 383 (the parent galaxy of 3C31). On the other hand, the modeling of the spectral characteristics of the radio emission of the central part of the radio galaxy 3C31 gives an estimate of the age of the central jet of about 100 million years. Therefore, it can be assumed that one of the possible reasons for the appearance or resumption of the radioactivity of the galaxy NGC 383 may be a triple close passage of galaxies. С целью выявления влияния окружающей среды на внегалактические радиоисточники, мы исследовали близкое окружение известной и хорошо изученной радиогалактики класса FRI 3C31. Показано, что около 110 млн лет назад галактики NGC 380 и NGC 386 располагались вблизи галактики NGC 383 (родительской галактики 3C31). С другой стороны, моделирование спектральных характеристик радиоизлучения центральной части радиогалактики 3С31 дает оценку возраста центрального джета примерно в 100 млн лет. Поэтому можно предположить, что одной из возможных причин появления или возобновления радиоактивности галактики NGC 383 может быть тройное близкое прохождение галактик.
Keywords: Astrophysics